The Border-making Policy of the Europe-an Union: Eastern Enlargement - MKRTCHYAN, LIKA (Journal of Education Culture and Society, 2020)
Having no internal borders, what is a border for the European Union (EU)? Which cri-teria does this powerful organization pursue in its decision-making on further expansion: geographical, political, cultural, economic or all of these? What is the profi t of the Union in advancing its external borders to the east? And why to the east and not the south or west across the Atlantic? Does it still mean that there is the reason for enlarging eastward based on the geographical belonging to Europe?1.This paper discusses the expansion of the European Union to the east with the main focus on its political and economic aspects of integration. The fi rst part includes intro-duction to the concept of Europe, historic background about the formation of the united Europe in terms of geography, culture, politics and economy, juxtaposing opinions and viewpoints of different experts and political scientists on “what is Europe?” and what are the core issues of its enlargement. The second and third parts are dedicated to the advan-tages and disadvantages of European Integration for both parties concerned – the EU and the candidate/member state, in the case of the former having its own “demarcation policy” towards certain regions of the continent when it comes to unifi cation. And the fourth part is about the communication and miscommunication of the informative bodies of the Euro-pean Union that are responsible for public awareness on any process that goes on within the European family. The lack of information results in the ignorance of citizens of Euro-pean and partner countries, which, of course, refl ects on the further processes of expansion on the political level and cultural perception and mentality on the social level.The conclusion sums up the research, and the bibliography lists the books, articles, monographs and Internet sources used in the course of the study.